2008
DOI: 10.3357/asem.2261.2008
|View full text |Cite
|
Sign up to set email alerts
|

Hypercapnia Effect on Core Cooling and Shivering Threshold During Snow Burial

Abstract: Hypercapnia significantly increased T(re) cooling rate by increasing respiratory heat loss but did not suppress shivering. Afterdrop may significantly contribute to hypothermia during rescue of avalanche burial victims.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 18 publications
3
32
1
2
Order By: Relevance
“…Exercise rewarms a person more rapidly than shivering, but may increase afterdrop (Giesbrecht and Bristow, 1997;Grissom et al, 2008). Warm, sugar-containing, nonalcoholic drinks may be given providing swallowing is possible.…”
Section: Stage I: Patient Alert and Shiveringmentioning
confidence: 97%
See 1 more Smart Citation
“…Exercise rewarms a person more rapidly than shivering, but may increase afterdrop (Giesbrecht and Bristow, 1997;Grissom et al, 2008). Warm, sugar-containing, nonalcoholic drinks may be given providing swallowing is possible.…”
Section: Stage I: Patient Alert and Shiveringmentioning
confidence: 97%
“…In 2001, a human experiment demonstrated that during breathing into artificial air pockets in snow, hypoxia and hypercapnia occur with a concomitant respiratory and metabolic acidosis within a few minutes, and the degree of hypoxia depends on the volume of the air pocket, snow density, and unidentified individual characteristics (Brugger et al, 2003). The combination of hypoxia, hypercapnia (Grissom et al, 2000(Grissom et al, , 2004(Grissom et al, , 2008, and hypothermia was termed ''triple H syndrome'' (Brugger et al, 2003). The cooling rate during snow burial is still debated.…”
Section: Air Pocket and Hypothermiamentioning
confidence: 98%
“…Survival of buried victims beyond this ‘asphyxiation phase’ requires the presence of a patent airway and of an air pocket surrounding the victim's upper airway as this will allow for some degree of oxygenation 17. While evading immediate asphyxia, buried victims with a patent airway will instead face gradually developing hypoxia, hypercapnia and hypothermia; termed the ‘triple H syndrome’ 18. The rate at which these changes occur depends on the volume of the air pocket and on snow density, but may start occurring within minutes 19.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, it is a common complication and a medical emergency that must be anticipated and treated aggressively 30. Avalanche victims may develop hypothermia rapidly, with documented mean cooling rates ranging from 0.8°C/h to 3°C/h,18 31 although individual case studies report extreme cooling rates of up to 9°C/h 24 32 33. The presence of hypercapnia will increase the rate of cooling, primarily by inducing hyperventilation and respiratory heat loss 18 34.…”
Section: Resultsmentioning
confidence: 99%
“…Improvised and commercial methods for preventing further body heat loss are being developed. [70][71][72][73][74][75] Arteriovenous anastomoses rewarming with or without negativepressure devices could offer a technique to rapidly rewarm severely hypothermic patients in the fi eld. [76,77] Resuscitation protocols for hypothermia and cardiac arrest have long engendered controversy, because of the resources that are required and the dismal recovery statistics.…”
Section: Hypothermiamentioning
confidence: 99%